"I beat my wife to correct her..." perpetration of intimate partner violence by men in low-income settings of Ibadan municipality: a qualitative exploration - Omowumi O. Okedare; Mobolaji M. Salawu; Olufunmilayo I. Fawole (Springer, 2024)
Abstract Background Globally, intimate partner violence (IPV) is a major public health problem. Recent studies have focused on women's experience of abuse. However, only few studies have documented men's perpetration of abuse in low-income countries. This study describes male perpetrated IPV and triggers of IPV among men in low-income communities of Ibadan, Nigeria. Methods This qualitative study adopted a descriptive phenomenology method to understand the lived IPV experience of men in Ibadan, southwest, Nigeria. The study was conducted in five communities selected by simple random sampling from a list of low-income communities within Ibadan municipal. Fourteen In-Depth Interviews (IDI) were conducted among eligible men aged 26 to 50 years, selected by convenience sampling. Interviews were transcribed verbatim. Thematic analysis was done to generate themes and sub-themes using NVIVO software. Results The forms of male perpetrated IPV included: physical, emotional, economic and controlling behaviour. Respondents also reported using money to control their wives. Sexual violence (marital rape) was not recognized as a form of IPV by the men interviewed. Participants disagreed that marital rape exist, because they believe that sex is an obligation of the wife to the husband. IPV was fostered by traditional marital expectations and ideals, norms that supported patriarchy, 'wife's disobedience', domestic financial challenges. Conclusion Men perpetrated different forms of violence against  their partners. IPV perpetration was encouraged by men's beliefs as well as the social norms. Interventions to educate men on the consequences of IPV on individuals, families and communities are recommended.